1993
DOI: 10.1007/bf00192091
|View full text |Cite
|
Sign up to set email alerts
|

The effect of growth rate and other growth conditions on the lipid composition of Escherichia coli

Abstract: Escherichia coli was grown as a continuous culture at various defined conditions of temperature, pH, aeration rate and dilution rate. The lipids were extracted from disrupted cells and the relative fatty acid content of the individual and total phospholipids was determined. The lipid composition of E. coli was shown to change with the fermentation conditions. Interestingly, E. coli adapted to high growth rates and to low oxygen tension by changing the lipid composition of the membrane in exactly the same way, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…For 6 and 48 h of growth, S ranged from 47 to 52% and 50 to 54%, respectively. This increase with prolonged cultivation and depletion of the growth substrate confirms earlier data obtained with P. putida P8 (35) and resembles data obtained with chemostat cultures of Escherichia coli at different dilution rates (2,55). Increased contents of saturated fatty acids enhancing the rigidity of the cytoplasmic membrane are a well-known mechanism of adaptation to strong membrane-fluidizing factors such as a rise in temperature, growth on or in the presence of lipophilic organic solvents, etc.…”
Section: Resultssupporting
confidence: 90%
“…For 6 and 48 h of growth, S ranged from 47 to 52% and 50 to 54%, respectively. This increase with prolonged cultivation and depletion of the growth substrate confirms earlier data obtained with P. putida P8 (35) and resembles data obtained with chemostat cultures of Escherichia coli at different dilution rates (2,55). Increased contents of saturated fatty acids enhancing the rigidity of the cytoplasmic membrane are a well-known mechanism of adaptation to strong membrane-fluidizing factors such as a rise in temperature, growth on or in the presence of lipophilic organic solvents, etc.…”
Section: Resultssupporting
confidence: 90%
“…Also, Chang and Cronan (10) demonstrated that cfa transcription in E. coli increased when cells were adapted to mildly acidic conditions. On the other hand, Arneborg et al (2) found that E. coli MT102 grown at pH 6.4 had lower proportions of unsaturated and cyclopropane fatty acids than did the same strain grown at pH 8.4. They demonstrated that E. coli increases the synthesis of saturated fatty acyl chains at the expense of both unsaturated and cyclopropane fatty acyl chains as a response to lower pH.…”
Section: Resultsmentioning
confidence: 97%
“…Homoviscous adaptation of the cytoplasmic membrane through alteration of membrane lipid composition maintains bacterial membranes in a functional, liquid crystalline state during heat stress (5,20,39). To determine whether an altered profile of membrane lipids contributes to the heat resistance of E. coli AW1.7, the membrane fatty acid composition of late-exponential-phase and heat-stressed cultures was compared to that of E. coli GGG10 ( Table 2).…”
Section: Resultsmentioning
confidence: 99%